Annual program development guidance and counseling in vocational high school - Rohiman, Iman; Farozin, Muh. (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
This study aims to generate annual program in vocational guidance and counseling to be used by teachers in vocational guidance and counseling. This study is a development using the 4D model (Define, Design, Depelovment, Dissemination). The instrument used in this study is a non-test instrument that is inventory development tasks. Data were analyzed and produce an annual program bimbinan and vocational counseling. This product is validated by expert guidance and counseling as well as in the validation by the practitioner / teacher guidance and counseling in schools. Data were analyzed quantitatively and qualitatively. The annual program of vocational guidance and counseling in the overall in both categories with some revisions based on advice and input from experts.